Synthesis and Spectral Studies of Some 2-Oxopyrimidine-1(2H)-yl]-pyrrolidine-2,5-dione Derivatives - Önal, Zülbiye (Asian Journal of Chemistry, 2012)
1-Amino-5-(4-methylbenzoyl)-4-(4-methylphenyl)pyrimidine-2(1H)-one/-thione (1a,b) reacted with various carboxylic anhydrides (2a-d) under different conditions and given the new amide and imide derivatives (3a-h). The newly synthesized compounds were characterized by elemental analysis, IR, 1H and 13C NMR spectral data. All the compounds were compared with their previous analogues.